Let it snow (movie tie-in) eaudiobook Three holiday romances. - Green, John (Listening Library, 2019)
Now a Netflix Original Film! New York Times  bestseller An ill-timed storm on Christmas Eve buries the residents of Gracetown under multiple feet of snow and causes quite a bit of chaos. One brave soul ventures out into the storm from her stranded train, setting off a chain of events that will change quite a few lives. Over the next three days one girl takes a risky shortcut with an adorable stranger, three friends set out to win a race to the Waffle House (and the hash brown spoils), and the fate of a teacup pig falls into the hands of a lovesick barista.   A trio of today’s bestselling authors—John Green, Maureen Johnson, and Lauren Myracle—brings all the magic of the holidays to life in three hilarious and charming interconnected tales of love, romance, and kisses that will steal your breath away. “A comedy as delicious as any whipped up by the Bard.” — Washington Post Book World Audiobook table of contents: The Jubilee Express , by Maureen Johnson, read by Rebecca Soler A Cheertastic Christmas Miracle , by John Green, read by Brandon Gill The Patron Saint of Pigs , by Lauren Myracle, read by Ali Ahn